ANALISIS TINGKAT KEBUGARAN JASMANI ATLET PUTRA ACCASIA FUTSAL PEKANBARU - Nur Rizky Dwi Augusta. BM; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine the level of physical fitness of the male athletes of Accasia Futsal Pekanbaru. This research is quantitative descriptive. The method used in this research is a survey method with test and measurement techniques. All athletes studied were measured by Indonesian physical fitness tests. The population in this study were 29 athletes of Accasia Futsal Pekanbaru and the sample in this study were male athletes of Accasia Futsal Pekanbaru, totaling 17 people. The instruments used in this research were the 60 meter sprint test, the body lift test for 60 seconds, the 60-second sit down test, the upright jumping test and the 1200 meter running test. The data in this study were obtained from tests and measurements made by the tester on the testee. The testee in this study were male athletes from Accasia Futsal Pekanbaru. Based on the results of research and data processing using physical fitness test norms and descriptive percentage formulas, it can be seen that the level of physical fitness that can be classified into good categories is 8 people with a percentage of 47.05%, in the moderate category as many as 6 people with a percentage of 35.29%, in the less category as many as 3 people with a percentage of 17.64% and no one has a very good and very poor classification. So if the average level of athlete's physical fitness is in the medium category with an average consideration of 15.94.Key Words: Physical Fitness Level